1993. The Contribution of Commensal Bacteria on the Severity of Symptoms During the 2017–2018 Influenza Season. (26th November 2018) - Ramamoorthy, Rohini; Thummathati, Soujanya; Stalons, Don; Huff, Matthew; Hassoun, Ali
Abstract: Background: Bacteria that are often a part of the microbiota of healthy individuals can produce not only a synergistic effect to establish infection with influenza virus but can also potentiate the severity of the infection and impact the patient's overall outcome. Methods: A retrospective chart review of patients diagnosed with Influenza infection using a multiplex PCR method that detects 9 different viruses and 14 bacteria was conducted. Data collected included demographics, results of culture and PCR data, need for pressor and ventilation and length of stay. Results: Of the 76 enrolled patients, 25 had a co-detected bacterial pathogen. In the co-detection group, 68% were males, 88% were Caucasian, mean age was 63, average BMI was 29, 32% were smokers, and 56% had been vaccinated. In the influenza only group, 37% were female, 65% were Caucasian, mean age was 67, average BMI was 28, 21% were smokers, and 52% had been vaccinated. Common presentations in the co-detected group included cough/SOB/and hypoxia in 92% vs. 80%. Pneumonia diagnosed in 85% of co-detections vs. 45%. H3N2 accounted for 68% of infections in the co-detected group vs. 58%. H1N1 in 8% vs. 16%. Influenza B was seen in 25% vs. 23%. MRSA was the most commonly detected bacteria (40%) and Streptococcus pneumoniae was 16%. In the co-detection group, only 24% of sputum cultures were positive with 100% concordance with PCR. Most common co-morbidities were DM 16% vs. 53%, COPD 24% vs. 19%, CKD 20% vs. 30%, CHF 20% vs. 37% in co-detections vs. influenza alone respectively. Co-detection patients needed pressor 12% vs. 4%, NPPV 20% vs. 12%, mechanical ventilation 36% vs. 14% and ICU admission 36% vs. 14%. Severe influenza was more common in the co-detection group 40% vs. 18%. Hypoxia and hypotension was seen in 92% vs. 63% and hypotension in 12% vs. 1% at ED arrival. Further, those with severe illness and co-detection, no predominant bacterial target was associated with severity. Those with co-detection had mortality of 20% vs. 6%. Average hospital LOS was 11 vs. 8 days. Conclusion: Detection of bacterial pathogens common to the respiratory microbiota by multiplex PCR in patients with Influenza infection might predict the severity of illness, potential morbidity, and mortality. Further studies are needed to confirm the above findings. Disclosures: D. Stalons, Diatherix: Employee, Salary. M. Huff, Diatherix: Research Contractor, Salary.